Two-Stage Treatment of a Large Pelvic Cystic Pseudotumor in a Metal-On-Metal Total Hip Arthroplasty - Cottino, Umberto; Dettoni, Federico; Risitano, Salvatore; Marmotti, Antonio; Rossi, Roberto (Joints, 2017)
The authors report a case of a huge cystic pseudotumor, surrounding a failed metal-on-metal total hip arthroplasty (THA). The cyst surrounded the hip anteriorly, occupied part of the anterior portion of the thigh, and extended to the anterolateral aspect of the abdomen. The case was treated by a two-stage procedure. The first stage consisted of a percutaneous drainage of the fluid content of the cyst (∼1,200 mL). This procedure reduced the risk of tearing the cyst capsule spreading the liquid in the tissues surrounding the THA, and in the abdomen. Thanks to this simple procedure, the second stage treatment consisted of a relatively usual THA revision. The patient recovered completely from the treatment and returned to pain-free full activities of daily living.
Keywords: Metal-On-Metal; pseudotumor; synovial cyst; total hip arthroplasty; revision surgery; two-stage technique